Podejście dynamiczne w badaniach ludzi młodych z perspektywy rynku pracy - aspekty poznawcze i aplikacyjne = Dynamic approach in research on young people from the perspective of labour market - cognitive aspects and applications - Grotowska-Leder, Jolanta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In the contemporary dynamically changing society, young generation, young people and youth undergo significant transformations. The mentioned categories are not clear-cut and they require clarification each time they are applied. Previous studies on young people, particularly young adults, have not revealed the complexity and internal diversification of their life experience, which limits the formulation of recommendations aiming to improve their life situation.
Keywords: młodzież; młodzi dorośli; rynek pracy; podejście dynamiczne; young adult; youth; labour market; dynamic approach